Study of High-Temperature Behaviour of ZnO by Ab Initio Molecular Dynamics Simulations and X-ray Absorption Spectroscopy - Bocharov, Dmitry; Pudza, Inga; Klementiev, Konstantin; Krack, Matthias; Kuzmin, Alexei (MDPI, 2021)
D.B., M.K. and A.K. acknowledge access to Piz Daint at the Swiss National Supercomputing Centre, Switzerland (CSCS) under the project ID sm02. The experiment at the MAX IV synchrotron was performed within the project 20190823. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; ZnO; zinc oxide; ab initio molecular dynamics; extended X-ray absorption fine structure